2014
DOI: 10.1155/2014/686109
|View full text |Cite
|
Sign up to set email alerts
|

Extract ofAntrodia camphorataExerts Neuroprotection against Embolic Stroke in Rats without Causing the Risk of Hemorrhagic Incidence

Abstract: In this study, the neuroprotective effect of an extract of Antrodia camphorata (A. camphorata), a fungus commonly used in Chinese folk medicine for treatment of viral hepatitis and cancer, alone or in combination with aspirin was investigated in a rat embolic stroke model. An ischemic stroke was induced in rats by a selective occlusion of the middle cerebral artery (MCA) with whole blood clots and then orally treated with A. camphorata (0.25 and 0.75 g/kg/day) alone and combined with aspirin (5 mg/kg/day). Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…In this regard, higher MDA level represents elevated oxidative stress and injury has been well-recognized. Our present observation indicated that Antrodia Camphorata can significantly inhibit free radicalmediated lipid peroxidation, and our present finding was in according with the previous investigation [9][10][11][12][13]18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this regard, higher MDA level represents elevated oxidative stress and injury has been well-recognized. Our present observation indicated that Antrodia Camphorata can significantly inhibit free radicalmediated lipid peroxidation, and our present finding was in according with the previous investigation [9][10][11][12][13]18].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in vivo study has indicated that Antrodia Camphorata not only can elevate hepatic glutathione-dependent enzymes upon protecting chemical-induced lesion on rat liver but also may decline oxidative injury conducted by toxic molecules of hydrogen peroxide [7]. On the other hand, previous experiment has indicated that cerebral ischemia-induced brain infarction and neurobehavioral disorder can be improved via administration of the traditional Chinese Medicine of Antrodia Camphorata [8][9][10][11][12]. As mentioned above, it seems likely to emphasize its beneficial effect here that Antrodia Camphorate may exactly exert its excellent antioxidant ability to alleviate further oxidative lesion.…”
Section: Introductionmentioning
confidence: 99%
“…All of the rats were kept at 37 °C in groups of five under a 12-h dark/light cycle with ad libitum access to food and water before the surgery. The rats were subjected to MCAO-induced ischemia by the administration of an autologous blood clot, as described in our previous studies [ 11 , 12 ]. After surgery, the rats were housed individually under similar environmental conditions and were found to be free of apparent infection or inflammation, as well as showing no neurological deficits.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that AC could effectively prevent serum-deprived apoptosis of PC12 cells by increasing phosphorylated ERK and decreasing phosphorylated JNK and p38, and by regulating a PKA/CREB-dependent pathway ( Huang et al, 2005 ; Lu et al, 2008 ). Oral treatment of AC extract provided neuroprotection in rats with thromboembolic stroke by reducing infarct volume, improves neurological outcome ( Lee et al, 2014 ). Furthermore, downregulation of iNOS/HO-1/Bax/caspase-3 and inhibition of hydroxyl radical formation were the main molecular pathways behind the AC neuroprotective activity against cerebral ischemia in rats ( Yang et al, 2015 ).…”
Section: Neuroprotection Potential Of Acmentioning
confidence: 99%